Escape from inequality: A relation insight on Chinese early education of verbal oppression and its reflections - Wencui, Zhang; Yajun, Fang; Hang, Zheng (Edelweiss Applied Science and Technology, 2025)
The article aims to disclose the relationship between the Chinese educational institutional environment and teachers’ management acts of verbal oppression to provide reflections on changing educational inequality. Employing the Stratified Analysis Method and the Key Success Factors Analysis Approach, it establishes a conceptual framework of verbal oppression and hierarchically explores the key causes and relational content. It has been found that the key causes behind teachers’ verbal oppression include language conflict, conquering desires, and institutional unequal relationships. There is a linear cause-effect relationship between the Chinese institutional education model and teachers’ verbal oppression, as well as an unequal relationship between teachers and children. The findings show that Chinese children’s early education of verbal oppression conceals a social institutional support given to teachers’ verbal oppression, which causes educational inequality. In conclusion, it encourages teachers to develop children’s communicative knowledge structure, rational intimacy personality, and anti-authority self-living habits to escape from educational inequality.